2013
DOI: 10.1177/1045389x13489781
|View full text |Cite
|
Sign up to set email alerts
|

A modeling and uncertainty quantification framework for a flexible structure with macrofiber composite actuators operating in hysteretic regimes

Abstract: Macrofiber composites are low cost, durable, and flexible piezoceramic devices that are presently being considered for applications that include shape control of airfoils for improved flight performance, vibration, and noise suppression and energy harvesting. However, macrofiber composites also exhibit hysteresis and constitutive nonlinearities that need to be incorporated in models and model-based control designs to achieve their full capability. In this article, we combine constitutive relations, constructed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Bayesian statistics are introduced to quantify material parameter uncertainty and the propagation of uncertainty when inversely identifying graphene TA model parameters in light of sound pressure data. This technique has shown to provide new insights into complex field coupled mechanics of other functional materials and adaptive structures 17,18 as well as a broader range of problems in weather and climate predictions, nuclear reactor design, and hydrology. 19 A three parameter TA model is often implemented based on prior results summarized by Arnold and Crandall.…”
Section: Introductionmentioning
confidence: 99%
“…Bayesian statistics are introduced to quantify material parameter uncertainty and the propagation of uncertainty when inversely identifying graphene TA model parameters in light of sound pressure data. This technique has shown to provide new insights into complex field coupled mechanics of other functional materials and adaptive structures 17,18 as well as a broader range of problems in weather and climate predictions, nuclear reactor design, and hydrology. 19 A three parameter TA model is often implemented based on prior results summarized by Arnold and Crandall.…”
Section: Introductionmentioning
confidence: 99%
“…It is also observed that there is an increase in the amplitudes of oscillations from 0°to 8°, which may be due to change in the aerodynamic loads at higher angles. The results also show that despite the wellknown hysteresis of piezoelectric MFC actuation [31], this behavior does not lead to measurably higher-order harmonics of the winglet actuator. It should be noted that future analysis of fluid-structure vortex interactions may require feedback control of both internal hysteretic constitutive behavior and compensation to external flow disturbances [32,33].…”
Section: Characteristics Of Winglet Oscillations Withoutmentioning
confidence: 68%
“…These methods construct a Markov chain which has the posterior distribution as its equilibrium distribution, bypassing the need for directly evaluating the integral in the denominator. This approach is used in Crews et al [2012] to estimate the parameters for a shape-memory alloy system and in Hu et al [2013] to estimate the parameters for an actuator constructed from macro-fiber composites.…”
Section: Parameteric Uncertainty Quantificationmentioning
confidence: 99%